The stresses around some unreinforced cutouts under various loading conditions - Houghton, D. S.; Rothwell, A. (College of Aeronautics, 1961)
A number of experimental results are given for unreinforced circular; elliptical and square cut-outs with rounded corners, under a variety of loading conditions. These results are then compared with the infinite flat plate solution, using the complex stress function and the method of conformal transformation. It is generally considered sufficiently accurate for a plane stress solution to be applied to problems of cut-outs in cylindrical shells, provided that the cut-out dimensions are small compared with the radius of curvature of the shell. In order to investigate this effect of shell curvature, a number of experiments were carried out on cutouts in two pressurised cylinders, and to obtain a wider range of loading conditions, a further series of experiments was conducted using a plane loading frame. Two aluminium alloy cylinders, of 44 in. and 60 in. diameter, were pressurised using air, and the stress conditions around the cutouts examined using electrical resistance strain gauge techniques. The plane loading frame enabled any combination of bi-axial tension and shear to be applied to a plane sheet containing the cut-out under examination. In this way the effects of body forces, which might arise in such applications as aircraft and nuclear reactors, could be simulated. The experimental results which are given generally show a close agreement with the theoretical plane stress solution.